Development of Teaching Materials of Demand, Supply and Balance Based on Digital Comic in Micro Economic Theory Course of Economic Education State University of Medan - Putri Sari Silaban; Aurora Elise Putriku; Sabda D.N Siahaan (PT FORMOSA CENDEKIA GLOBAL, 2022)
In general, this study aims to determine the level of feasibility and effectiveness of digital comic-based Demand, Supply and Balance teaching materials with material in microeconomic theory courses that can improve student learning outcomes. This study uses research and development (R&D) methods using the ADDIE model. This research was conducted on fourth semester students who took microeconomic theory courses in the economic education study program in the 2021/2022 academic year. For a small trial sample, 10 students were taken by random sampling. The developed teaching materials received a good assessment from the experts with an average feasibility score of 89.3 in the very feasible category. In the practical test, students also gave a positive response with an overall average score of 89, 3 in the category of very practical. In the effectiveness test, students also gave a positive response with an overall average score of 26.89 in the category of very effective.